Regional health inequalities in Australia and social determinants of health: analysis of trends and distribution by remoteness - Joanne Flavel; Sophie Kedzior; Vivian Isaac; Darryl Cameron; Fran Baum (Rural and Remote Health, 2024)
Introduction: Rural and remote areas have a higher burden of disease, leading to inequalities in health between regional and urban areas. This article compares trends in health status and social determinants of health (SDH) in capital cities and the remaining areas of (rest of) states and territories in Australia, and examines the distribution of health and social determinants between metropolitan, inner regional, outer regional, rural and remote areas. Methods: We conducted an ecological analysis of Public Health Information Development Unit data for Australian capital cities, the rest of states and territories, and local government areas (LGAs). Trends in inequalities in capital cities and the rest of states and territories (regional, rural and remote) from 1986 to 2018 were assessed using the slope index of inequality. Data for 538 LGAs were classified into remoteness categories and scatterplots produced to assess differences in health and SDH both between and within remoteness categories. Results: Our analysis of trends found that premature and avoidable mortality and infant mortality decreased in all socioeconomic quintiles outside of capital cities. However, inequality in socioeconomic area disadvantage increased for premature and avoidable mortality. There were mixed trends in terms of SDH: higher increases in full-time participation in secondary education and internet access in the most disadvantaged quintiles led to decreases in inequality in urban and non urban areas. Inequality increased outside capital cities for income indicators, rental stress and labour force participation due to higher proportional gains for areas within the least disadvantaged quintile of area disadvantage. Inequality was higher in capital cities compared to the rest of states and territories in 2016 for rental and mortgage stress, welfare-dependent families and participation in tertiary education. It was higher in the rest of states and territories compared to capital cities for premature and avoidable mortality, labour force participation and internet access. We found that while rural and remote areas had worse health and SDH on average, there was heterogeneity in premature and avoidable mortality and SDH for outer regional, remote and very remote LGAs. Conclusion: Increasing inequality in health and SDH in outer regional, rural and remote areas underscores the ways in which health inequalities strongly correlate with inequalities in SDH. Variation in health and SDH within non-metropolitan areas suggests it may not be appropriate to clump regions and towns together when conducting analysis in Australia. Policies to improve rural and remote health need to enhance existing provisions of social and health infrastructure, with context-specific measures to reduce these health inequalities.